COMPARATIVE PLANETARY MINERALOGY: IMPLICATIONS OF MARTIAN AND TERRESTRIAL JAROSITE. A CRYSTAL CHEMICAL PERSPECTIVE - Papike J.J.; Karner J.M.; Shearer C.K. (My University, 2006)
The importance of the discovery of jarosite at the Meridiani Planum region of Mars is discussed. Terrestrial studies demonstrate that jarosite requires a unique environment for its formation, crystallizing from highly acidic (pH < 4) S-rich brines under highly oxidizing conditions. A likely scenario for jarosite formation on Mars is that degassing of shallow magmas likely released SO2 that reacted with aqueous solutions in shallow aquifers or on the martian surface. This interaction forms both H2SO4 and H2 S. A martian oxidant must be identified to both oxidize H2S to produce the required acidity of the fluid, and to oxidize Fe2+ to Fe3+. We suggest that reactions involving both sulfur and the reduction of CO2 to CO may provide part of the answer. The jarosite crystal structure is truly remarkable in terms of its tolerance for the substitution of a large number of different cations with different ionic radii and charges. The structure accommodates hydrogen, oxygen, and sulfur, the stable isotope systematics of which are strong recorders of low-temperature fluid-rock-atmosphere interactions. Jarosite has been proven to be a robust chronometer for Ar-Ar and K-Ar dating techniques, and there is every reason to believe that U-Pb, Rb-Sr, and Nd-Sm techniques for older jarosite from Mars will also be robust. Although the discovery of jarosite on Mars alone, with no other analytical measurements on the phase, has given us insights to martian surficial processes, the true power of jarosite can not be exploited until jarosite is sampled and returned from Mars. Mars sample return is a long way off but, until then, we should be vigilant about examining martian meteorites for alteration assemblages that contain jarosite. A suite of jarosite samples representing a significant time span on Mars may hold the key to reading the record of martian atmospheric evolution. © 2005 Elsevier Inc. All rights reserved.